Effects of valsartan compared with telmisartan in reducing insulin resistance on type 2 diabetes mellitus (T2DM) patients with hypertension - Hemi Sinorita; Luthfan Budi Purnomo; R.Bowo Pramono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Insulin resistance is a major risk factor for patients with type 2 diabetesmellitus (T2DM). Telmisartan and valsartan are angiotensin II type I receptorblockers (ARBs) that are often used in patients with metabolic syndrome andT2DM. This study aimed to compare the effect of valsartan and telmisartan inreducing insulin resistance on T2DM with hypertension. Patients of T2DM wereopen-label screened at the Endocrinology Policlinic, Department of InternalMedicine, Dr. Sardjito General Hospital, Yogyakarta, and then randomized intotwo groups. The first group received valsartan 80 mg per day up to 160 mg perday, the second group received telmisartan 40 mg per day up to 80 mg per dayin addition with life-style modifying and diabetes therapy. Homeostasis modelassessment of insulin resistance (HOMA-IR), triglyceride and HDL cholesterollevels of patients were measured before and after receiving telmisartan andvalsartan for 12 weeks. A total of forty-nine outpatients were involved in thisstudy comprised of 25 female patients (51%) and 24 male patients (49%) with27 patients (55.1%) received telmisartan and 22 patients (44.9%) receivedvalsartan as the hypertension therapy. No significantl difference were observedbetween telmisartan group compared with valsartan group in HOMA-IR (14.01± 16.39 vs. 5.31 ± 3.51; p=0.053), triglyceride levels (165.71 ± 94.70 vs 144.41 ±48.33 mg/dL; p=0.620), HDL-C level (48.57 ± 9.78 vs 49.24 vs 49.24 ± 12.56 mg/dL;p=0.999). In conclusion, telmisartan demonstrated no difference compared tovalsartan in reducing insulin resistance on T2DM patients with hypertension.